Our Civilizing Mission The Lessons of Colonial Education (Volume 60) - Harrison, Nicholas (Liverpool University Press, 2019)
Our Civilizing Mission is at once an exploration of colonial education and a response to current anxieties about the historical and conceptual foundations of the 'humanities'. On the one hand, it treats colonial education as a facet of colonialism. It draws on a rich body of work by 'colonized' writers - starting with Edward Said, then focusing on Algeria - that attests to the suffering inflicted by colonialism, to the shortcomings of colonial education, and to the often painful mismatch between the world of the colonial school and students' home cultures. On the other hand, it asks what can be learned by treating colonial education not just as an example of colonialism but as a provocative, uncomfortable example of education, and its powers of transformation.'This is a deeply insightful, stimulating and scholarly book - uncompromisingly reflective, finely argued and carefully referenced, it deepens our understanding of colonial education and legacies in a number of mutually enriching ways that consistently draw out complexity and urge us to think about the teaching of literature. This is a book that will last the test of years and will prompt better scholarship (and, possibly, classroom practice) from the rest of us.'Patrick Crowley, University College Cork